2011
DOI: 10.1007/s12028-011-9572-1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring cerebral autoregulation after head injury. Which component of transcranial Doppler flow velocity is optimal?

Abstract: Systolic flow indices (Sx and Sxa) demonstrated a stronger association with outcome than the mean flow indices (Mx and Mxa), irrespective of whether CPP or ABP was used for calculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 27 publications
1
69
0
Order By: Relevance
“…35 However, a cohort study of 300 patients with head injury showed that Sxa had a stronger association with outcome than Mxa. 31 Relationship of Continuous Indices, Sxa and TOxa, with Transient Hyperemic Response Ratio Both Sxa and TOxa showed good accuracy for predicting impaired autoregulation as seen by a THRR of p1.09, without significant differences between the two methods. However, the correlations between THRR and Sxa and TOxa were relatively poor, in keeping with previous reports from head injury.…”
Section: Methodological Considerationsmentioning
confidence: 93%
See 4 more Smart Citations
“…35 However, a cohort study of 300 patients with head injury showed that Sxa had a stronger association with outcome than Mxa. 31 Relationship of Continuous Indices, Sxa and TOxa, with Transient Hyperemic Response Ratio Both Sxa and TOxa showed good accuracy for predicting impaired autoregulation as seen by a THRR of p1.09, without significant differences between the two methods. However, the correlations between THRR and Sxa and TOxa were relatively poor, in keeping with previous reports from head injury.…”
Section: Methodological Considerationsmentioning
confidence: 93%
“…Furthermore, THRT in prospective observational studies was shown to be useful in predicting clinical deterioration after SAH. 2,6 However, while clinical and experimental data exist supporting the validity of Sxa and TOxa, 13,23,25,31,32,34 neither index has been evaluated for its power to predict DCI. The mean flow index, Mx, which is derived from mean FV and CPP and its noninvasive version, Mxa, where ABP is used instead of CPP, have been previously investigated in patients with SAH.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations